2017
DOI: 10.1016/j.chemosphere.2017.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of toxic metals and organic micro-pollutants in sediments from tropical urban rivers, Kinshasa, Democratic Republic of the Congo

Abstract: The increasing contamination of fresh water resource by toxic metals and Persistence Organic Pollutants (POPs) is a major environmental concern globally. In the present investigation, surface sediments collected from three main rivers named, Makelele, Kalamu and Nsanga, draining through the city of Kinshasa, Democratic Republic of the Congo, were characterized for grain size, organic matter, toxic metals, POPs (including organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 52 publications
1
48
2
2
Order By: Relevance
“…Contrary to PCBs, we observe significant positive correlations between OM/TOC and ƩOCPs (Table S9), indicating that sediment OM and TOC could enhance the adsorption of these compounds and therefore affect their transport and redistribution in sediments. OCPs in SMR sediments samples were close to those found in the Bahlui River, Romania (Dragan et al, 2006), Ravi River, Pakistan (Syed et al, 2014) and River Po, Italy (Viganò et al, 2015), higher than those found in the Tonghui River, China (Zhang et al, 2004), Durance River and Arc River, France (Kanzari et al, 2012(Kanzari et al, , 2015), but lower than those observed in tropical urban rivers, Congo (Kilunga et al, 2017) (Table S11).…”
Section: Distribution and Sources Of Ocpssupporting
confidence: 58%
See 1 more Smart Citation
“…Contrary to PCBs, we observe significant positive correlations between OM/TOC and ƩOCPs (Table S9), indicating that sediment OM and TOC could enhance the adsorption of these compounds and therefore affect their transport and redistribution in sediments. OCPs in SMR sediments samples were close to those found in the Bahlui River, Romania (Dragan et al, 2006), Ravi River, Pakistan (Syed et al, 2014) and River Po, Italy (Viganò et al, 2015), higher than those found in the Tonghui River, China (Zhang et al, 2004), Durance River and Arc River, France (Kanzari et al, 2012(Kanzari et al, , 2015), but lower than those observed in tropical urban rivers, Congo (Kilunga et al, 2017) (Table S11).…”
Section: Distribution and Sources Of Ocpssupporting
confidence: 58%
“…As ecologically and economically important water bodies for human living, riverine ecosystems have attracted the interest of authorities and researchers, especially after the continuous development of urban, industrial and agricultural activities, which have released into these ecosystems large amounts of contaminants (Islam et al, 2015;. Among these anthropogenic contaminants, metals, polycyclic aromatic hydrocarbons (PAHs) and persistent organic pollutants (POPs) such as polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) have caused deep concern for both developed and developing countries due to their toxicity, persistence, bioaccumulation, high long-range atmospheric transport and potentially adverse health effects on wildlife and humans (Kilunga et al, 2017;Resongles, 2014). Human activities such as mining, smelting, traffic emissions, industrial sewage and agriculture are the main sources of metals in sediments (Besser et al, 2008;Odhiambo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The PCA analysis provides additional support for a common source of Zn, Pb and Cd as several species of these heavy metals demonstrated a significant loading weight on PC1. Previous studies indicated that these metals could have a common source and similar transport pathways in urban rivers (Kilunga et al, 2017). Although significantly correlated with the other metals, Cu showed a different spatial pattern and high loading on PC2, which suggests a contrasting pollution source.…”
Section: Distribution and Source Analysis Of Heavy Metal Speciationmentioning
confidence: 81%
“…Metal concentrations in the Wen-Rui Tang River sediments were also elevated compared to several other rivers and lakes locally and globally (Table S2): Cu 3e14 Â , Zn 4e36 Â , Pb 1.1e10 Â times, and Cd 4e880 Â times higher than the concentrations in these other watersheds. Heavy metal contaminations in river sediments were much severer than that in Congo, which was identified with slight heavy metal pollution (Mwanamoki et al, 2014;Kilunga et al, 2017). In contrast, Cr concentrations were at levels similar to sediments from Dong Ting Lake (China), Yangtze River (China) and Red River (Vietnam), but 20 times higher than that in the Sinú River (Colombia).…”
mentioning
confidence: 88%
“…nitrate and Cr(VI) coexisting in groundwater using 3-dimensional bio-electrochemical systems (BES) has been achieved, but it still needs applied potentials [16].Aquatic sediment acts as a repository for multiple pollutants in rivers and lakes, and as a significant source of internal pollutants. Pollutants include organic matter, metal contaminants, and inorganic salts [17][18][19]. Organic substances play an important role in the deterioration of water quality because when it catabolized, the dissolved oxygen in water consumed, thus results in an anoxic or anaerobic condition of water.…”
mentioning
confidence: 99%